Implementation of Sensitive Method for Determination of Benzophenone and Camphor UV Filters in Human Urine - Veronika Gomersall; Katerina Ciglova; Jana Pulkrabova (Toxics)
The level of the human body’s burden of benzophenone and camphor ultraviolet (UV) filters can be estimated from their urinary levels. The present study describes the implementations and validation of the sensitive analytical method for the analysis of seven benzophenone and two camphor UV filters in urine. Sample preparation includes overnight enzymatic hydrolysis and ethyl acetate extraction followed by purification by dispersive solid-phase extraction using a sorbent Z-Sep. For the analysis, ultra-high performance liquid chromatography coupled with tandem mass spectrometry was used. Validation was performed using a Standard Reference Material® 3673 and an artificially contaminated urine sample. Target analyte recoveries ranged from 79–113% with repeatability expressed as a relative standard deviation of 2–15%. The limits of quantification were between 0.001 and 0.100 ng/mL in urine. This method was subsequently applied to examine the urine samples collected from Czech women. The analytes benzophenone-1 and 4-hydroxy-benzophenone were the most common analytes present in 100% of the samples, whereas benzophenone-3 was quantified in only 90% of the urine samples. The other four determined benzophenone derivatives were quantified in ≤33% of the samples. The derivatives of camphor were not detected in any samples. This method could be applied in biomonitoring studies.